Rhinocerebral mucormycosis: a case series - Walikar, Basavaraj N.; Patil, Anand N.; Madraki, Raveendra M.; Biradar, Wasifa S.; K., Yashaswini (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: The study is aimed to evaluate the role played by predisposing conditions like diabetes mellitus and precipitating factors like renal failure are discussed briefly here. Methods: The prospective study of treatment of rhinocerebral mucormycosis on dialysis for renal failure without control subjects was evaluated. Subjects were patients with uncontrolled diabetes with renal failure presenting with rhinocerebral mucormycosis. Complete blood count, renal function tests, CT scan of paranasal sinuses and brain, nasal endoscopy and biopsy was done in all the 10 patients. Results: Seven patients were on long term dialysis except one patient who was on dialysis for the first time. Amphotericin was started for all 10 patients. Seven patients who were on long term dialysis did not recover from mucormycosis and succumbed to death (70% patients showed 30.71±17.18 days prognosis). Three patients (30% patients), who were not on dialysis and had a lesser degree of renal failure, responded to aggressive antifungal and surgical debridement treatment, and recovered from infection. Conclusions: Mucormycosis in patients on dialysis is fatal. Improvement in renal function is a favourable prognostic factor for the successful treatment of mucormycosis.